2020
DOI: 10.1051/shsconf/20207404025
|View full text |Cite
|
Sign up to set email alerts
|

Methods of eliminating waste from food packaging as a globalization tool

Abstract: The article deals with possible ways of elimination of waste from food packaging. It focuses on eliminating packaging waste through unpackaged food stores and the zero waste concept. Elimination of any waste in the form of packaging is an important element of protection and reducing the burden on the environment, and in this context also important element of globalization. The methodological approach is based on a field survey in the form of interviews with customers of a selected packaging-free shop and resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Regarding the identified advantages, the research is in line with previous research (Price, Waterhouse & Co, 2015;Salkova & Regnerova, 2020) in the advantages of waste elimination, reduction of environmental impact, quality of products sold and reuse of packaging. In addition, however, it revealed the advantage of "being able to buy the exact quantity required".…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Regarding the identified advantages, the research is in line with previous research (Price, Waterhouse & Co, 2015;Salkova & Regnerova, 2020) in the advantages of waste elimination, reduction of environmental impact, quality of products sold and reuse of packaging. In addition, however, it revealed the advantage of "being able to buy the exact quantity required".…”
Section: Discussionsupporting
confidence: 81%
“…Research into the disadvantages of shopping in zero-packaging stores confirmed the conclusions come to by Beitzen-Heineke et al ( 2017) and Salkova and Regnerova (2020), that the main disadvantages are the limited range of products, unavailability and a small number of stores and higher demands on the preparation of the shopping. In addition, it revealed other relatively important disadvantages, in particular the "necessity to bring your own containers", "higher price of products sold", "hard-to-observe hygiene requirements" and "uncertainty of the composition and quality of products".…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…According to [18], public-private partnership can become an effective mechanism for reforming economic relations. For the state, this is a great opportunity to implement many promising projects in industry and in housing and communal services.…”
Section: Examples Of Digital Ecosystemsmentioning
confidence: 99%
“…The purpose of the packaging itself is to protect the product. However, in their attempts to make the product look attractive, people resorted to excessive packaging, leading to a waste of resources-an issue people should take into consideration [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%